Puncture characterization of multilayered polypropylene homopolymer/ethylene 1-octene copolymer sheets. Issue 16 (1st February 2016) - He, Guansong; Zhang, Fengshun; Yu, Huaning; Li, Jiang; Guo, Shaoyun
Abstract : Both the puncture strength and energy of the multilayered sheets were significantly higher than those of the conventional blend. Abstract : This paper presents the studies of the puncture resistances of conventional blend and multilayered structure sheets. The polypropylene homopolymer (HPP)/ethylene 1-octene copolymer (POE) alternating multilayered sheets were prepared though multilayered coextrusion. Polarized optical microscope (POM) photographs revealed that HPP and POE layers aligned alternately vertical to the interfaces and continuously parallel to the extrusion direction, indicating a better laminate structure. Puncture results demonstrated the conventional blend was less puncture-resistant than the multilayered samples. Obvious interfacial delamination occurred in the multilayered structure during crack propagation, causing the puncture behavior to develop into a staged rupture behavior. Hence the puncture resistance was enhanced by the special energy absorbing mechanisms including the plastic deforming independently, interfacial delamination and ductile tearing of the layers.